2012
DOI: 10.1108/01443581211222662
|View full text |Cite
|
Sign up to set email alerts
|

Do happiness and foreign aid affect bilateral migrant remittances?

Abstract: Purpose -Studies on the determinants of remittances focus primarily on a single country or undertake cross-country analyses using aggregate data. By comparison, there is a dearth of empirical evidence on the determinants of remittances from multiple host to multiple destination countries. To address this deficiency, the purpose of this paper is to use a novel dataset which captures these bilateral flows. Design/methodology/approach -The paper concentrates on three sets of explanatory variables: those which cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…According to the narrative, poor countries value development aspects like happiness more. This is broadly consistent with an evolving stream of the literature on happiness and wellbeing in the economics of development assistance (Arvin and Lew, , b, , , b).…”
supporting
confidence: 83%
“…According to the narrative, poor countries value development aspects like happiness more. This is broadly consistent with an evolving stream of the literature on happiness and wellbeing in the economics of development assistance (Arvin and Lew, , b, , , b).…”
supporting
confidence: 83%
“…It resulted in household members were not concern to much about household expenses, and it affected to happiness of the household. (Arvin, and Lew, 2002) 4.4 Level of investment from the remittance showed that households with different levels of investment from remittance would have significant difference toward capital utilization with statistically significant at the 0.01 level. Considering pairwise comparison, household that had high level of investment would have more capital utilization than household that had medium level of investmentt and household that had low level of investment.…”
Section: Household Type;mentioning
confidence: 98%
“…As discussed, the earlier inflow of remittance has serious implications on macroeconomic fluctuations in international trade, exchange rate, and overall economic growth that led to the rising/fall of immigration pattern (Corden and Neary, 1982;Rajan and Subramanian, 2005;Amuendo-Dorentas and Pozo, 2004;Lillo and Garay, 2019;Bettin et al, 2015;Arvin and Lew, 2012;Walmsley et al, 2007). Corden and Neary (1982) and Rajan and Subramanian (2005) argue that the prevalence of Dutch disease in the destination country leads to an appreciation of exchange rate and a lesser inflow of remittance to the origin country in the case of Latin American countries.…”
Section: Literature Reviewmentioning
confidence: 99%